REPUTAȚIA ÎNTREPRINDERII ÎN CONTEXTUL CONCURENȚEI NELOIALE – O VARIABILĂ CONSTANTĂ - Moraru, Iulian (CEP USM, 2020)
The undertking's reputation is an inherent dimension of establishing and / or consolidating a favorable / unfavorable position in the context of a progressive market economy. On the background of the alternating reputation of undertakings is situated the concept of competition as an economic rivalry between two or more undertakings on different markets. The dynamics of the evolution of undertakings' reputation is directly proportional to the loyalty shown by companies in the competition process. The manifestation of an unfair attitude by the undertakings involved in that process is a considerable premise in determining the change in their reputation. Thus, the reputation of undertakings is the finality of their conduct in the relevant competitive relationships. Therefore, unfair competition is the right framework for establishing, consolidating or declining the reputation of the undertakings involved in the competitive process. Taking into account the above mentioned facts, it can be stated that the topicality of the researched subject is an indisputable one, or the competitive process is a continuous one, fact which implies the corresponding susceptibility to variation of the reputation of the market players. The ultimate aim of this research is the author's intention to identify the role and place of the dimension of the undertakings's reputation and its impact on the system of unfair competition actions. The primary research methods used are legalcomparative and logical-formal. The anticipated results consist in formulating relevant conclusions to the subject to be researched, as well as possible further research directions and / or suggestions for amending the legislation
Keywords: establishment; concurența neloială